Residual stress analysis in sustainable structural integrity assessment of an engineering component - Sayeed Hossain, Mohammad; Maleque, Md. Abdul (Elsevier, 2018)
A good description of residual stress is a key to the accurate structural integrity assessment of an engineering component and can particularly have an influence on the life extension of an engi-neering component. Several methods and tools exist for determining residual stresses. These are categorized by invasive and non-invasive techniques. Invasive techniques are widely available and are mechanical strain relief techniques. However, when using mechanical strain relief tech-niques to measure residual stress in an engineering component containing a highly triaxial residual stress field close to yield extra care must be taken since the creation of a free surface as part of the measurement procedure can lead to plastic redistribution of the residual stress field. The elastic inversion algorithms of the experimental procedure does not usually account for the plastic redistribution. This chapter demonstrates finite element analysis application to illustrate the effect of the plastic redistribution on the measured residual stresses and to obtain a more accurate stress anal-ysis. Previous measurements using a semi-destructive technique are compared with the results of a simulated measurement method on a 316H stainless steel welded pipe containing a repair weld offset from a girth weld to illustrate the effect of plastic redistribution on the measured result. A modification to the measurement method was further analyzed and validated using finite element simulation of a butt-welded pipe.